2023
DOI: 10.1007/s10787-022-01129-1
|View full text |Cite
|
Sign up to set email alerts
|

A cellular and molecular biology-based update for ivermectin against COVID-19: is it effective or non-effective?

Abstract: Despite community vaccination against coronavirus disease 2019 (COVID-19) and reduced mortality, there are still challenges in treatment options for the disease. Due to the continuous mutation of SARS-CoV-2 virus and the emergence of new strains, diversity in the use of existing antiviral drugs to combat the epidemic has become a crucial therapeutic chance. As a broad-spectrum antiparasitic and antiviral drug, ivermectin has traditionally been used to treat many types of disease, including DNA and RNA viral in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 122 publications
0
6
0
Order By: Relevance
“…Hence, as long as more reliable data emerge from randomized trials with sufficient size, dose, and duration, healthcare providers should refrain from prescribing ivermectin to treat or prevent COVID-19. Also, combined treatment of ivermectin with other drugs may minimize adverse effects and demonstrate its therapeutic efficacy in the treatment of COVID-19, as we suggested in our previous study [25]. Thus, we hope that this hypothesis will encourage further investigations and consideration of the possible prophylactic roles of ivermectin against Omicron and future variants of SARS-CoV-2 to save the lives of many people and prevent hospitalization and morbidity.…”
Section: Countrymentioning
confidence: 61%
See 2 more Smart Citations
“…Hence, as long as more reliable data emerge from randomized trials with sufficient size, dose, and duration, healthcare providers should refrain from prescribing ivermectin to treat or prevent COVID-19. Also, combined treatment of ivermectin with other drugs may minimize adverse effects and demonstrate its therapeutic efficacy in the treatment of COVID-19, as we suggested in our previous study [25]. Thus, we hope that this hypothesis will encourage further investigations and consideration of the possible prophylactic roles of ivermectin against Omicron and future variants of SARS-CoV-2 to save the lives of many people and prevent hospitalization and morbidity.…”
Section: Countrymentioning
confidence: 61%
“…Table 2. Clinical trials investigated the anti-COVID-19 effects of Ivermectin [25]. Also, in simultaneous use of ivermectin, some drugs have been proposed to reduce its side effects.…”
Section: Role As An Ionophorementioning
confidence: 99%
See 1 more Smart Citation
“…Recent research revealed that IVM may inhibit the lipopolysaccharide-induced production of inflammatory cytokines via the inhibition of importin α/β, a pathway of protein transport into the nucleus. It is also reported that ivermectin targets host inflammatory pathways like nuclear factor kappa-lightchain-enhancer of activated B cells (NF-κB), Akt kinase/mammalian target of rapamycin (AKT/mTOR), and signal transducer and activator of transcription 3 (STAT3) [15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…
Dear Editor, Nowadays, a number of studies suggest that patients with primary diseases such as multiple cancers are more susceptible to severe Coronavirus disease-2019 (COVID-19) and mortality [1][2][3]. Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is responsible for COVID-19 infection and has a variety of cell and organ targets [4].
…”
mentioning
confidence: 99%